Experimental Study on Partial Replacement of Clayey Soil with Rice Husk on Side Skew Bricks - Tholkapiyan, M.; Manikandan, S.; Rajasegar, M.; Malar Mannan, A. (International Journal of Engineering and Technology, 2018)
Bricks are composed of inorganic non-metallic material and are widely used as building components all over the world. All the conventional clay bricks depend on good quality clay available from agricultural fields presuming a weight of 3kg per brick. The main objective of this study is to investigate the effects of rice husk addition, on the compressive strength ,water absorption, density, efflorescence and thermal conductivity properties of fired side skew clay bricks.Â Brick raw material and rice husk obtained from Poochiathipedu, Thiruvallur were used. Mix proportions for the clay brick were carried as per the guidelines. Rice husk was substituted by volume 5% Rice husk, 10% Rice husk and 15% Rice husk to brick raw material and was casted in the form of side skew and standard rectangular bricks.we are adopting side skew brick according to IS 1526-1960 table 1 to get an maximum reflection of incident solar radiation. Application of thermal insulation as an energy saving method is more effective in the region between tropic of cancer and equator.Â This concept plays an crucial role in the energy consumption of a building.Â Green building often includes measure to reduce energy consumption service such as cooling in tropical region.The 5% of side skew rice husk combination shows increase in strength while the combination of the 5% rectangular brick shows notable variation with respect to the standard side skewÂ